Comparative study of percutaneous radiofrequency ablation and hepatic resection for small, poorly differentiated hepatocellular carcinomas. Issue 10 (21st November 2013) - Iida, Hiroya; Aihara, Tsukasa; Ikuta, Shinichi; Yamanaka, Naoki
<x xml:space="preserve">Abstract</x> Aim Histologically, poorly differentiated hepatocellular carcinomas (HCC) are considered highly malignant. Here, we aimed to evaluate the relative efficacy and safety of hepatic resection or radiofrequency ablation (RFA) for treating this malignancy. Methods Between April 2004 and May 2011, we enrolled 48 patients who had poorly differentiated HCC that had been diagnosed postoperatively by pathological assessment. All the tumors had a maximum diameter of 3 cm and all patients had three or less tumors. Fifteen of these patients underwent hepatic resection (HR group) and 33 patients underwent RFA (RF group). The patient background, tumor characteristics, overall survival rate and recurrence‐free survival rate were assessed in both groups. Results The mean maximum tumor diameter was 2.5 and 2.0 cm in the HR and RF groups, respectively. The prothrombin activity level was 94% and 86% in the HR and RF groups, respectively. The 1‐, 3‐ and 5‐year cumulative survival rates were 89.1%, 68.7% and 68.7%, respectively, in the HR group, and 59.2%, 40.9% and 32.7%, respectively, in the RF group. The 1‐, 3‐ and 5‐year recurrence‐free survival rates were 85.1%, 64.8% and 48.6%, respectively, in the HR group, and 29.0%, 7.2% and 7.2%, respectively, in the RF group. There was a significant difference between these groups (P < 0.05). Conclusion As hepatic resection has greater efficacy than RFA in the treatment of poorly differentiated HCC, even in cases with a small tumor size, we recommend its use for this malignancy.